Feasible Environmental Kuznets and Institutional Quality in North and Southern African Sub-regions - Egbetokun, Samuel; Osabuohien, Evans S.; Akinbobola, Temidayo (International Journal of Energy Economics and Policy, 2018)
One of the goals of Africa as a developing continent is to grow and also reduce environmental pollution. Most studies investigate the presence of inverted U-shaped Environmental Kuznets Curve (EKC) using pollutants such as Carbon dioxide (CO2), the use of point pollutants such as Suspended Particulate Matter (SPM) is not so popular in literature. Similarly, most studies that assess the role of institutions in the income-pollution nexus do not investigate their capability in achieving feasible turning on the EKC. Focusing on three pollutants, namely: CO2, nitrogen oxide (N2O) and SPM, this study employs system generalised method of moments (SGMM) to assess the role of institutions in two sub-regions (North and Southern Africa) in attaining EKC turning points. Results, among others, indicate that the both sub-regions did not attain a level of average income capable of turning EKC round for CO2 and N2O but do for SPM. It is also revealed that Southern Africa attained EKC faster than North Africa. It is therefore recommended that for the purpose of achieving the goal of green growth, the institutional quality should be strengthened in the two Africa sub-regions, particularly in Southern Africa. Keywords: Economic growth; EKC; Environmental pollution; Institutional quality; Land degradation; North Africa; Southern Africa. JEL Classifications: O13; O44; Q56